1983
DOI: 10.1139/v83-250
|View full text |Cite
|
Sign up to set email alerts
|

Methylmercury(II) sulfhydryl interactions. Potentiometric determination of the formation constants for complexation of methylmercury(II) by sulfhydryl containing amino acids and related molecules, including glutathione

Abstract: Formation constants for the interaction of methylmercury(II) with 2-mercaptoethanol, mercaptoacetic acid, O-methyl-mercaptoacetate, 2-mercaptosuccinic acid, L-cysteine, D,L-penicillamine, N-acetyl-D,L-penicillamine, glutathione, thiocholine, and 4-mercapto-N-methylpiperidine have been determined by potentiometric titration. For the equilibrium [Formula: see text], log β occurs in the range 14.60(1)–17.14(1), with the lowest value obtained for the cationic complex of thiocholine, [Formula: see text]. Acid disso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 12 publications
1
23
1
Order By: Relevance
“…The experimental pK a 's for this set of organic thiols are listed in Table 1 and range from 4 to 12 pK a units. [65][66][67][68][69][70][71][72][73][74][75][76] The test calculations in Figure 1 indicate that there is a large error in the calculation of the pK a 's for simple thiols. In previous studies on nucleobases, we found that the methods that performed well for pK a 's of cation-neutral pairs often performed poorly for pK a 's of neutral-anion pairs.…”
Section: Resultsmentioning
confidence: 99%
“…The experimental pK a 's for this set of organic thiols are listed in Table 1 and range from 4 to 12 pK a units. [65][66][67][68][69][70][71][72][73][74][75][76] The test calculations in Figure 1 indicate that there is a large error in the calculation of the pK a 's for simple thiols. In previous studies on nucleobases, we found that the methods that performed well for pK a 's of cation-neutral pairs often performed poorly for pK a 's of neutral-anion pairs.…”
Section: Resultsmentioning
confidence: 99%
“…[2] and using these values for k3 and Kdp yielded a value of log kw = 17.16 f 0.05. The formation constants calculated for the deprotonated 1 : I complex and the 2: 1 complex (eqs.…”
Section: Chemicalsmentioning
confidence: 99%
“…2. Equilibrium constants were obtained from titration data using a version of MINIQUAD (12) by procedures described previously (2).…”
Section: Potentiometric Determination Of Formation Constantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the logarithm of stepwise protonation constants (log K) should vary linearly as a function of the reciprocal of the dielectric constant of the medium. It is observed that in DMF media the log K values of MSA, dopa and phen increase linearly as a content of organic containing pure water as a solvent [28][29][30][31] but small differences are possibly due to the different experimental procedures ,temperature and different background electrolytes used. In this study the linear variation of log K values as a function of 1/D (figure 8) in mixtures shows that the dominance of electrostatic interactions.…”
Section: Effect Of Solvent:-mentioning
confidence: 99%